Three Essays on International Credit Market and Monetary Policy - (:unkn) unknown (My University, 2017)
My dissertation studies the behavior of international credit flow and the associated monetary policy spillover effect. In the first chapter, I am interested in decomposing the long-run variations and the short-run variations of US dollar denominated credit in emerging market economies. This paper uses a multivariate correlated unobserved component model to study the dynamic relationship among dollar credit in emerging market economies, US interest rates and the dollar index. The results from this model suggest that the transitory shocks to dollar credit in emerging market economies are highly negatively correlated with the transitory shocks to the US interest rate and the transitory shocks to the dollar index. The estimate of the cyclical component of dollar credit well captures the recent boom and bust phase in emerging market. The rise in non-financial corporate overseas debt issuance has been playing a critical role in international capital flow activities. The second chapter of my dissertation examines the determinants of corporate overseas bond issuance in 32 countries during 1993-2015. The results suggest that the compression in risk premium has encouraged the corporates in emerging markets to borrow from international bond markets. This effect is more prevalent in countries with tighter international capital control policies, so that corporates outside financial regulation serve as surrogate financial intermediaries at the border. These incentives suggest a potential systematic shift in international financial risk transmission through corporate fixed-income markets and a possible external shock channeled through the monetary policy spillover effect. The third chapter investigates further into the relative strengths of the global, regional, and country-idiosyncratic factors in driving debt dollarization in global financial market. Using a dynamic factor model, we decompose the fluctuations in the dollar debt growth of 12 countries into a global factor, a developed economy factor, an emerging market factor, and country-specific factors. We find that, since 2009, the global factor of the dollar debt growth has been increasing dramatically. It is the global factor that plays the dominant role in explaining the dollar debt growth of these countries.
Keywords: Business Cycle; Global Liquidity; International Finance; Macroeconomics; Monetary Policy; Time Series Econometrics